How home health nurses plan their work schedules: A qualitative descriptive study. Issue 21 (23rd July 2018) - Irani, Elliane; Hirschman, Karen B; Cacchione, Pamela Z; Bowles, Kathryn H
Abstract : Aims and objectives: To describe how home health nurses plan their daily work schedules and what challenges they face during the planning process. Background: Home health nurses are viewed as independent providers and value the nature of their work because of the flexibility and autonomy they hold in developing their work schedules. However, there is limited empirical evidence about how home health nurses plan their work schedules, including the factors they consider during the process and the challenges they face within the dynamic home health setting. Design: Qualitative descriptive design. Methods: Semi‐structured interviews were conducted with 20 registered nurses who had >2 years of experience in home health and were employed by one of the three participating home health agencies in the mid‐Atlantic region of the United States. Data were analysed using conventional content analysis. Results: Four themes emerged about planning work schedules and daily itineraries: identifying patient needs to prioritise visits accordingly, partnering with patients to accommodate their preferences, coordinating visit timing with other providers to avoid overwhelming patients, and working within agency standards to meet productivity requirements. Scheduling challenges included readjusting the schedule based on patient needs and staffing availability, anticipating longer visits, and maintaining continuity of care with patients. Conclusion: Home health nurses make autonomous decisions regarding their work schedules while considering specific patient and agency factors, and overcome challenges related to the unpredictable nature of providing care in a home health setting. Future research is needed to further explore nurse productivity in home health and improve home health work environments. Relevance to clinical practice: Home health nurses plan their work schedules to provide high quality care that is patient‐centered and timely. The findings also highlight organisational priorities to facilitate continuity of care and support nurses while alleviating the burnout associated with high productivity requirements.